Analysis of Institutional Collaboration In Handling Violations of Neutrality of State Civil Apparatus at The Concurrent General Elections - setiawan, andi (Unnes Political Science Journal, 2023)
This research examines how relations between institutions are developed and managed by a state institution which in this case is the Electoral Supervisory Body of the Republic of Indonesia, through the establishment of an Institutional Network in handling neutrality violations of the State Civil Apparatus (SCA) at the Concurrent General Election in 2019. This research has several background issues, including the SCA neutrality issue as one of the three main problems in each election moment. In the 2019 election, there were several results and allegations of electoral irregularities in 1,096 instances of suspected violations of the independence of the State Civil Apparatus. Another issue is that the Electoral Supervisory Body is responsible for overseeing the neutrality of SCA, but there is hampered by limited authority which is the Electoral Supervisory Body cannot give punishment on SCA, they just allowed to providing recommendations. This analysis is focused on the Network Governance Theory by Klijn, Koppenjan, & Termeer. This theory is applied through a two-step strategy, each of which has three indicators. The research method used is a descriptive research that will generate qualitative findings. The results of this study found that of the six indicators contained in Network Governance Theory, the Institutional Network of the Electoral Supervisory Body only applied five of the six indicators of Theory. The other indicators are not applied for some reasons. Through the Game Management and Network Structuring Strategy that is contained in this Network Governance Theory, this Institutional Network produces two outputs, which are Memorandum of Understanding and the Cooperation Agreement that governs and binds between the two institutions namely Electoral Supervisory Body and The State Civil Apparatus Commission.